Impact of Antidepressants on Weight Gain: Underlying Mechanisms and Mitigation Strategies - Mouawad, Michael; Nabipur, Leena; Agrawal, Devendra K. (Archives of Clinical and Biomedical Research, 2025)
Antidepressants are widely prescribed for major depressive disorder and anxiety, yet their long-term use is associated with weight gain, affecting up to 55-65% of patients. This adverse effect contributes to treatment discontinuation, relapse, and worsened metabolic health outcomes, including increased risk for obesity and type 2 diabetes. This article presents a critical evaluation of the published reports on the mechanisms underlying antidepressant-induced weight gain, comparative effects across drug classes, and mitigation strategies. Weight gain varies significantly by antidepressant class. Tricyclic antidepressants, monoamine oxidase inhibitors, and a tetracyclic antidepressant, mirtazapine, are associated with the most substantial weight increases, while selective serotonin reuptake inhibitors typically induce weight gain after prolonged use. Mechanisms involve serotonergic and dopaminergic signaling, receptor desensitization, insulin resistance, and altered leptin and ghrelin levels. Genetic factors, including CYP2C19 metabolizer status, and lifestyle factors such as baseline body mass index and diet, further influence risk. Bupropion, a norepinephrine-dopamine reuptake inhibitor, is the only commonly prescribed antidepressant consistently associated with weight loss or neutrality. Mitigation strategies include switching medications, adding agents like metformin or GLP-1 receptor agonists, and incorporating behavioral interventions. Antidepressant-induced weight gain is a multifactorial issue requiring individualized management. Understanding pharmacologic mechanisms and patient-specific risk factors is essential for optimizing treatment efficacy while minimizing metabolic burden.